2019
DOI: 10.1126/sciadv.aax1853
|View full text |Cite
|
Sign up to set email alerts
|

Salt creeping as a self-amplifying crystallization process

Abstract: Salt creeping is a ubiquitous phenomenon in which crystals precipitate far from an evaporating salt solution boundary, which constitutes a major problem in outdoor electronics, civil engineering, artworks, and agriculture. We report a novel experimental approach that allows to quantitatively describe the creeping mechanism and demonstrate its universality with respect to different salts. We show that there exists a critical contact angle below which salt creeping occurs, provided also the nucleation of multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 25 publications
3
35
0
Order By: Relevance
“…Previously, wetting the upper molecular layers of a silicon (1,0,0) surface with water was simulated (Barisik and Beskok, 2013;Ozcelik et al, 2020); the researchers observed the water spread beyond the drop boundary. The nanometre-sized crystals observed centimetres away from the creeping front were considered a proof of precursor nanofilms (Qazi et al, 2019). Our findings not only confirm such nanofilms in CsCl solutions but also reveal their formation around salty ices at temperatures above the salts' eutectics.…”
Section: Precursor Nanofilm Formed Below 0 °Csupporting
confidence: 74%
See 1 more Smart Citation
“…Previously, wetting the upper molecular layers of a silicon (1,0,0) surface with water was simulated (Barisik and Beskok, 2013;Ozcelik et al, 2020); the researchers observed the water spread beyond the drop boundary. The nanometre-sized crystals observed centimetres away from the creeping front were considered a proof of precursor nanofilms (Qazi et al, 2019). Our findings not only confirm such nanofilms in CsCl solutions but also reveal their formation around salty ices at temperatures above the salts' eutectics.…”
Section: Precursor Nanofilm Formed Below 0 °Csupporting
confidence: 74%
“…5i). Evidently, a precursor nanofilm (De Gennes, 1985) of the liquid brine (which could not be detected with the ESEM) had spread over the silicon surface to these remote locations, and, after the evaporation of water from the brine, the small salt crystals emerged (Qazi et al, 2019). A similar behaviour characterizes the non-seeded and seeded samples below the Teu, as presented in chapter 3.2.5.…”
Section: Sublimation Above the Teumentioning
confidence: 69%
“…4). One can wonder whether this surface colonization process has to do with salt creeping, 20 i.e., seen here as the lateral development of the efflorescence from the previous efflorescence salt crystals or simply results from crystallization in new pores at the ceramic surface, as in Ref. 19, for instance, or a mix of both processes.…”
Section: A Salt Crystallization Dynamics: the Efflorescence Exclusion Zonementioning
confidence: 99%
“…For solutes of low solubility, the patterns left by evaporative crystallization are similar to “coffee-ring” patterns formed by evaporation of a particle-laden drops ( 11 , 12 , 16 ). However, when the dissolved mass is excessive, three-dimensional crystal structures may arise ( 17 , 18 ). In particular, when a drop containing saturated sodium chloride is evaporated on a hydrophobic surface, “salt globes” form because of the propensity of crystals to nucleate at the air/water interface ( 18 ).…”
Section: Introductionmentioning
confidence: 99%